2011
DOI: 10.1016/j.bbrc.2011.10.121
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanins regulate the protrusive activities of cell membrane

Abstract: Tetraspanins have gained increased attention due to their functional versatility. But the universal cellular mechanism that governs such versatility remains unknown. Herein we present the evidence that tetraspanins CD81 and CD82 regulate the formation and/or development of cell membrane protrusions. We analyzed the ultrastructure of the cells in which a tetraspanin is either overexpressed or ablated using transmission electron microscopy. The numbers of microvilli on the cell surface were counted, and the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 35 publications
(54 reference statements)
1
66
0
Order By: Relevance
“…In relation to the cell surface topology, tetraspanins regulate membrane microextrusions (Fig. 2) [79,80]. Forced expression of CD82 reduces the formation and development of microextrusions, while Cd82 ablation potentiates them, probably by altering membrane bending and/or membranecytoskeleton interaction [14,55].…”
Section: Membrane Microextrusionsmentioning
confidence: 98%
“…In relation to the cell surface topology, tetraspanins regulate membrane microextrusions (Fig. 2) [79,80]. Forced expression of CD82 reduces the formation and development of microextrusions, while Cd82 ablation potentiates them, probably by altering membrane bending and/or membranecytoskeleton interaction [14,55].…”
Section: Membrane Microextrusionsmentioning
confidence: 98%
“…While most tetraspanin proteins are predominantly present on the plasma membrane, CD63 is mostly present on the surface of endosomes. It has been reported that CD63 has a tendency to generate large protein domains on the inner surface of late endosomes that can change the physical properties of the membrane in a manner that encourages invagination (Piccin, Murphy et al 2007, Bari, Guo et al 2011). An additional mechanism for exosome biogenesis involves the accumulation of the bioactive lipid ceramide in the endosomal membrane (Trajkovic, Hsu et al 2008).…”
Section: Exosome Biogenesismentioning
confidence: 99%
“…How does the presence of M6B on the Schwann cell microvilli affect the structure of the underlying axonal membrane? Tetraspanin proteins are involved in the formation of various tubular cell membrane structures including microvilli (Singethan & Schneider-Schaulies, 2008;Bari et al, 2011). They regulate cell morphogenesis by altering the membrane curvature, as well as by mediating membrane-dependent cytoskeletal reorganization.…”
Section: Discussionmentioning
confidence: 99%